Physicochemical Parameters and Phytoplankton Diversity of Kware Lake, Nigeria - I.M, Magami; A.D, Ibrahim; A.U, Mani; A.W, Abubakar; S.M, Zakari (The International Journal of Biotechnology, 2015)
Kware Lake is a popular natural lake in Sokoto which is used for domestic purposes, irrigation practices, and fisheries. Anthropogenic activities are routine at the catchment area. In this study, water and phytoplankton samples were collected for five months. Standard procedures were adopted for determination of physicochemical parameters viz; temperature, depth, turbidity, nitrogen, phosphorus, dissolved oxygen (DO), biological oxygen demand (BOD), etc. These parameters were observed to have varied within the period of study. Five species of phytoplankton were identified, and Volvox globator was recorded the highest percentage distribution during the study. The irregular fluctuations and variations observed between the parameters studied do not exceed the limit approved by WHO and EPA.